A RICE OF INTENSIFICATION SYSTEM BASED ON MICROCONTROLLER-BASED RICE OF INTENSIFICATION: SISTEM KONTROL PENGAIRAN SAWAH MENGGUNAKAN METODE SISTEM RICE OF INTENSIFICATION BERBASIS MIKROKONTROLLER - Adi Candra; Farida Farida; Husni Sulaiman (ITP Press, 2022)
Agricultural irrigation is an effort made by farmers to maintain the consistency of water availability on agricultural land. However, the use of water, especially in the dry season, cannot be properly regulated so that the use of water for irrigating rice fields is not in accordance with the needs. Water regulation is made with the aim of being able to meet water needs evenly on each land, information from several Mattirobulu farmer groups in Dampang Village, Gantarang District, Bulukumba Regency, information is obtained that, until now the distribution of irrigation water through irrigation gates is done manually, so that the distribution of water in paddy fields didn’t go as expected due to the presence of several farmer groups and the presence of several irresponsible people or persons committing fraud in the distribution of water. So that problems arise such as the loss of mutual trust between farmers, to the occurrence of disputes between farmers. The purpose of this research is to design a prototype of a rice field irrigation control system using a microcontroller-based Rice of Intensification system. The results of this study are the use of a greedy algorithm to determine the lowest point that can function properly to determine the closest point in the water level detection system. Utilization of the water level sensor to detect the height of the water level in the fields can detect well with a low level of 1 cm, a medium level of 5 cm and a high level of 10 cm.